WiFi hacking : wireless penetration testing for beginners (Packt Publishing, 2018)
"This course includes an overview of the various types of wireless (802.11) networks, available encryption security systems (WEP, WPA, and WPA2), and how to use open-source tools to hack and crack these vulnerable wireless (WiFi) networks. Since their introduction in 1999, wireless networks have been rapidly expanding in their usage and availability. Unfortunately, many people believe these wireless networks are designed as a secure solution for sharing data, but this is rarely the case. In this course, you will gain a deeper understanding of the WEP, WPA, and WPA2 wireless security protocols, and how to exploit their vulnerabilities in order to gain access to any wireless network during a penetration test. You will use this information to increase the security of your networks and to implement a better defensive security posture to prevent an attacker from accessing your networks."--Resource description page